2017
DOI: 10.1371/journal.pone.0182053
|View full text |Cite
|
Sign up to set email alerts
|

Differences in biopsychosocial profiles of diabetes patients by level of glycaemic control and health-related quality of life: The Maastricht Study

Abstract: AimsTailored, patient-centred innovations are needed in the care for persons with type 2 diabetes mellitus (T2DM), in particular those with insufficient glycaemic control. Therefore, this study sought to assess their biopsychosocial characteristics and explore whether distinct biopsychosocial profiles exist within this subpopulation, which differ in health-related quality of life (HRQoL).MethodsCross-sectional study based on data from The Maastricht Study, a population-based cohort study focused on the aetiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
2
16
0
1
Order By: Relevance
“…Socio-economic factors like employment status, income, and educational status showed significant associations with HRQoL on bivariate analysis, but not on multivariable analysis. Similar associations have been reported previously in patients with diabetes [ 37 , 38 ] and underline the need for tailored clinico-social interventions in specific subgroups to improve health outcomes. However, since most studies have been cross-sectional in nature, it is also unclear whether employment and income levels are the cause or effect of DPN and HRQoL status.…”
Section: Discussionsupporting
confidence: 87%
“…Socio-economic factors like employment status, income, and educational status showed significant associations with HRQoL on bivariate analysis, but not on multivariable analysis. Similar associations have been reported previously in patients with diabetes [ 37 , 38 ] and underline the need for tailored clinico-social interventions in specific subgroups to improve health outcomes. However, since most studies have been cross-sectional in nature, it is also unclear whether employment and income levels are the cause or effect of DPN and HRQoL status.…”
Section: Discussionsupporting
confidence: 87%
“…We found no impact of anticoagulation [55], antihypertensives (no comparable data), mood stabilisers [55], and NSAIDs [59] on HRQoL. For the routine laboratory findings, we found that HbA1c (%) negatively impacted MH, aligning with the glycaemic control literature [60,61], but that the levels of proteinuria and anti-dsDNA antibodies were not related to HRQoL [7,26,62,63]. An increasing C3 level led to higher SF; however, the levels or hypocomplementemia of C3 or C4 did not influence any other HRQoL item.…”
Section: Discussionsupporting
confidence: 60%
“…Our work corroborates the influence of socioeconomic position on intermediate health outcomes in patients with diabetes, even in a region with one of the lowest health inequality levels of Spain [ 25 ], a country that, in turn, has relatively low health inequality compared to other European countries [ 23 ]. Apart from SES-related individual characteristics that could favour results in patients with higher SES, such as healthy diet [ 44 , 45 ], physical activity [ 46 ], medication adherence [ 47 ], social support [ 44 , 46 ] or self-efficacy [ 48 ], there are also contextual factors, such as the way health care institutions are organized and the health policies they adopt, that could differentially affect patients according to their SES level [ 21 ]. This differential influence may occur even in health care systems that provide universal coverage, such as the Spanish health system, where some organizational barriers, such as copayments, may pose greater obstacles for people of lower SES [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%